Interpersonal Meaning in Billie Eilish Interview: Hit Me Hard and Soft Album - Putri Farida Nur Afifah; Nurholis; Irman Nurhapitudin (Faculty of Language and Literature, University of Surakarta, 2025)
This study aims to examine conversation in interviews with Billie Eilish about her new album by identifying mood systems, speech functions, and the interpersonal relationship that Billie Eilish built with the interviewer. The research employs a descriptive qualitative method with a discourse analysis approach and document analysis as the data collection technique. According to the findings of this study, the most common mood type is declarative mood, followed by interrogative mood (polar and wh-interrogative mood), imperative mood, and exclamative mood. Meanwhile, the most common speech function is a statement. Furthermore, to be aware of how Billie Eilish establishes interpersonal relationships by examining mood and residue, combining mood types, applying the speech function, and the interacting contract. Studying interpersonal meaning may help us understand how language can produce meaning in a social context and how the interaction between Billie Eilish and the interviewer.